Metabolic power and efficiency for an amputee cyclist: implications for cycling technique - Elmer, S. J.; Martin, J. C. (Journal of Applied Physiology, 2021)
Cycling technique is steeped in cultural lore. One deeply held belief is that "pulling up" to lift the leg (increased muscular leg flexion) will optimize technique and improve efficiency. In contrast, scientific evidence suggests that when cyclists are instructed to pull-up efficiency decreases. However, such interventions may not have allowed sufficient time for cyclists to adapt and refine their technique. This case study documented how a cyclist with a complete unilateral limb amputation consumed metabolic power to produce mechanical power during single-leg cycling. The cyclist was a four time US National Paralympic Champion who performed single-leg cycling for 7 yr and thus was fully adapted to pull up. We hypothesized that a counterweight system, which reduced the requirement to pull up, would decrease metabolic power and increase efficiency for this cyclist. The cyclist performed submaximal cycling (100, 135, 170, 205 W, 80 rpm, 5 min) with and without a counterweight (10 kg) on the unused crank. Expired gases were measured, and metabolic power and gross efficiency were calculated. Metabolic power decreased on average by 87 ± 7 W (P < 0.001) and gross efficiency increased from 16.3 ± 1.9 to 18.0 ± 1.8% (P < 0.001) when cycling with the counterweight. During counterweighted single-leg cycling, the metabolic power of unloaded cycling decreased (317 vs. 238 W) and delta efficiency was similar (25.2 vs. 25.5%). Results demonstrated that significant metabolic power was associated with pulling up to produce muscular leg flexion power even in a cyclist who pulled up substantially during cycling. Our findings confirm observations from previous studies that altered pedaling technique acutely and indicate that pulling up during cycling is less efficient.NEW & NOTEWORTHY This study offers unique insight into pedaling technique and provides the "final nail in the coffin" to the notion that pulling up improves cycling efficiency. When the requirement for pulling up was reduced with the counterweight, the cyclist immediately benefited as the cost to move the limb decreased and gross efficiency increased. These case study results along with previous research suggest that, in general, cyclists should not adopt pedaling techniques, which increase the action of pulling up.